Perception of Fresh undergraduate students to library and information services in academic libraries: case study of university of Ibadan (2011)
This survey examined the perception of users to library and information services in academic libraries. A structured questinnaire was developed and validated to elicit information from 300 sample population selected to reflect the entirety of the case study. Four hypotheses were developed and tested using chi square statistical methods at 0.05 significance level. The findings showed that inadequate communication between the library and its users as well as inability of the academic libraries to acquire relevant infrastructures and update thier libraries with current information were all factors responsible for the ways users perceive the services offered by the academic libraries. Based on the findings recommendations were made that academic libraries should have full internet connectivity to enhance effective communication between the library and its users as well as organize regular orientation sessions for all categories of libray users in order to update thier knowloegde with new services available in the library as well as information technology applications and usage relating to library services